2019
DOI: 10.3928/23258160-20190129-04
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Retinal Nonperfusion Associated With Posterior Segment Neovascularization in Diabetic Retinopathy Using Ultra-Widefield Fluorescein Angiography

Abstract: BACKGROUND AND OBJECTIVE: To quantify the size and location of nonperfusion associated with posterior segment neovascularization (NV) in proliferative diabetic retinopathy (PDR) using ultra-wide- field fluorescein angiography. PATIENTS AND METHODS: Cross-sectional study of 18 eyes with PDR. The total image area, areas of nonperfusion, buds of posterior segment neovascularization (either neovascularization of the disc or elsewhere), and the distances from each bud to the nearest area of nonperfusion and to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…The association between DR and diabetic nephropathy, two important microvascular complications of DM, has been actively investigated, and the results have implied an intimate relationship between the manifestations and severity of DR and renal function and its progression in patients with DM. 5,6,8,9,[22][23][24][25][26] Retinal capillary nonperfusion is a major sign of microvascular insufficiency of DR, reflecting the extent of ischemia and is directly involved in development of PDR, the end stage of DR. 14,16,18,27 Ultra-widefield imaging has enabled more thorough assessments of retinal vascularity including the far peripheral retina, therefore enabling a more precise assessment of the NPA in DR eyes. [14][15][16]18,28 In this study, we measured retinal NPAs quantitatively on UWFA in an objective manner and analyzed their correlation with renal function in patients with type 2 DM with DR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between DR and diabetic nephropathy, two important microvascular complications of DM, has been actively investigated, and the results have implied an intimate relationship between the manifestations and severity of DR and renal function and its progression in patients with DM. 5,6,8,9,[22][23][24][25][26] Retinal capillary nonperfusion is a major sign of microvascular insufficiency of DR, reflecting the extent of ischemia and is directly involved in development of PDR, the end stage of DR. 14,16,18,27 Ultra-widefield imaging has enabled more thorough assessments of retinal vascularity including the far peripheral retina, therefore enabling a more precise assessment of the NPA in DR eyes. [14][15][16]18,28 In this study, we measured retinal NPAs quantitatively on UWFA in an objective manner and analyzed their correlation with renal function in patients with type 2 DM with DR.…”
Section: Discussionmentioning
confidence: 99%
“…The recent introduction of ultrawidefield imaging has enabled more detailed analyses of NPA by covering most of the retinal area. 15,16 Microvascular pathology also plays an important role in development of renal insufficiency in diabetic nephropathy. 17 Considering the proven relationship between DR and nephropathy, microangiopathy associated with DM in the kidney, hence, renal function and proteinuria, can be correlated with microangiopathy in the retina, presented as retinal capillary NPA, proving that this can have clinical advantages.…”
mentioning
confidence: 99%
“…An association between NP areas and risk for the development of PDR has been reported in recent studies using UWF FA. Baxter et al [13] demonstrated that a NP threshold size greater than 23% of the retinal image is associated with posterior segment NV. Nicholson et al [14] also suggested that at least 107.3 DA of NP are at risk of proliferative disease.…”
Section: Discussionmentioning
confidence: 99%
“…NV was defined as a focal area of leakage on the angiogram, with a characteristic appearance of fine loops or a network of vessels [13]. UWF FA images taken prior to the appearance of leakage or showing minimal leakage (between 20-45 s) were chosen for analysis of numbers and areas of NVs to avoid erroneous enlargement of the measured area.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation